Tenascin-C a novel regulator of brain tumor-initiating cells (BTIC) in glioma acts through NOTCH - Miyake, Juliano Andreoli; Vooijs, Marc (Translational Cancer Research, 2017)
Glioblastoma is the most common and malignant adult brain tumor. Standard treatment consists of temozolomide (TMZ), surgery and radiotherapy (RT) (1). However, despite multimodal treatment, the average survival of patients with glioma is between 9–12 months after initial diagnosis, and tumor recurrence is almost 100% (2). The main characteristics of glioma are: high rates of cell proliferation; highly invasive and infiltrative across the surrounding vessels, myelinated fibres and areas of necrosis and highly angiogenenic. Glioblastoma is composed by heterogeneity cells; some cells have a genetic and cellular heterogeneity characteristic in human tumor. It is important to identify these subpopulations of tumor cells with stem-cell like characteristics (3) because these cells are related with treatment resistant and glioma recurrence (4). Understanding these cells characteristics and their metabolism are important to design new treatments against glioma.